Policy challenges to community energy in the EU: A systematic review of the scientific literature. (November 2021) - Busch, Henner; Ruggiero, Salvatore; Isakovic, Aljosa; Hansen, Teis
Abstract: In response to the ongoing climate crisis, many countries have issued policies to support the uptake of renewable energy. In the same vein, the European Union (EU) has issued a revised renewable energy directive in 2018. One of the pillars of the directive is the support for community energy initiatives, i.e. sustainable energy initiatives run by or with the participation of citizens. The concept of community energy (CE) has been linked to a number of advantages, such as strengthening local democratic processes or economic development for marginalised communities. The aim of this review article is to find out how past policies helped to overcome or aggravated transition challenges towards a higher share of community energy in the EU. To answer this question, we reviewed the scientific literature on community energy from the last decade. We analysed this body through a theoretical lens that highlights four main transition challenges. These occur in relation to 1) directionality, 2) demand articulation, 3) experimentation, 4) policy learning & coordination. Our results show that visions and goals are important policy tools for providing directionality in the energy transition. Feed-in-tariffs (FiT) surface as the most important policy to support community energy projects and spark demand. We found very little indication for a link between community energy and explicit experimentation. Nevertheless, learning does take place amongst peers. Our review underlined the important role intermediaries play in facilitating policy learning and coordination. We conclude by presenting a number of concrete policy recommendations such as strengthening intermediary organisations and providing administrative support to community energy initiatives in case of changes in the policy framework. Highlights: Community Energy requires favourable policies to overcome transition challenges. Feed-in-Tariffs are a wide-spread tool to support community energy projects. Policy frameworks need to leave room for local visions. Intermediaries have supported community energy initiatives.